Factors Related To The Successful Breastfeeding Of Exclusive Breastfeeding At Bidan Ritta's Clinic, Depok - Diah Argarini; Retno Widowati; Luthfiah Qolby Shalsabilla (Universitas Malahayati, 2022)
ABSTRACT Exclusive breastfeeding is the best nutrition for babies in the first six months of life for healthy growth and development. Many factors are believed to influence the success of exclusive breastfeeding. To analyze the factors related to the success of exclusive breastfeeding in the birth clinic of Bidan Ritta’s Depok. Correlative descriptive research with a quantitative approach. The sampling technique was carried out by total sampling with a total of 35 respondents. The instrument of this research used a questionnaire. The statistical test used is the Chi-Square test that this study can be trusted with an error rate of 0.05 and the Spearman rank test. The results of the study the majority of respondents gave exclusive breastfeeding by 80%. The results showed that the knowledge variable with exclusive breastfeeding had a p-value of 0.036, the attitude variable with exclusive breastfeeding had a p-value of 0.10, the work variable with exclusive breastfeeding had a p-value of 0.275 and the husband's support variable with exclusive breastfeeding had a p-value of 0.036. The success rate of exclusive breastfeeding at the Bidan Ritta’s Clinic is high. Factors related to the success of breastfeeding include the knowledge, attitude and support of the husband, while the work factor is not related to the success of exclusive breastfeeding. It is necessary to improve health promotion regarding the benefits and understanding of exclusive breastfeeding to mothers and husbands. Keywords: Knowledge, Attitude, Husband's Support, Work, Exclusive Breastfeeding ABSTRAK ASI eksklusif merupakan nutrisi terbaik untuk bayi pada masa enam bulan pertama kehidupan untuk pertumbuhan dan perkembangan yang sehat. Banyak faktor yang dipercaya dapat mempengaruhi keberhasilan pemberian ASI eksklusif ini. Tujuan penelitian ini untuk menganalisis faktor-faktor yang berhubungan dengan keberhasilan pemberian ASI eksklusif di klinik bersalin Bidan Ritta Depok. Penelitian deskripstif korelatif dengan pendekatan kuantitatif. Teknik pengambilan sampel dilakukan dengan cara total sampling dengan jumlah 35 responden. Instrument penelitian ini menggunakan kusioner. Uji statistic yang digunakan adalah uji Chi-Square bahwa penelitian ini dapat dipercaya dengan tingkat kesalahan 0,05 dan uji rank spearman. Hasil penelitian mayoritas responden memberikan ASI eksklusif sebesar 80%. Hasil penelitian menunjukkan bahwa variabel pengetahuan dengan ASI eksklusif hasil p-value 0,036, variabel sikap dengan ASI eksklusif hasil p-value 0,10, variabel pekerjaan dengan ASI eksklusif nilai p-value 0,275 dan variabel dukungan suami dengan ASI eksklusif hasil p-value 0,036. Tingkat keberhasilan pemberian ASI eksklusif di Klinik Bidan Ritta adalah tinggi. Faktor yang berhubungan dengan keberhasilan pemberian ASI antara lain faktor pengetahuan, sikap dan dukungan suami sedangkan faktor pekerjaan tidak berhubungan dengan keberhasilan pemberian ASI eksklusif. Perlu meningkatkan promosi kesehatan mengenai manfaat dan pengertian ASI eksklusif kepada pada ibu dan suami. Kata Kunci : Pengetahuan, Sikap, Dukungan Suami, Pekerjaan, ASI Eksklusif